1996
DOI: 10.1007/bf01874924
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-rich cells in the branchial epithelium of the teleost,Oreochromis mossambicus, acclimated to various hypotonic environments

Abstract: Branchial mitochondria-rich (MR) cells were examined on the afferent side of gill filaments in tilapia (Oreochromis mossambicus) acclimated to different hypotonic environments, local fresh water (LFW), hard fresh water (HFW) and 5‰ salt water (SW). Scanning electron micrographs (SEM) identified three types of apical surfaces of the MR cells, wavy convex, shallow basin and deep hole. In spite of the different types of apical surfaces, light microscopic (LM) and transmission electron microscopic (TEM) studies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
57
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 48 publications
(27 reference statements)
15
57
1
2
Order By: Relevance
“…The extent of emergent MRC proliferation observed in C. v. variegatus and C. v. hubbsi is comparable to that observed in other euryhaline teleosts (Lee et al, 1996;Scott et al, 2004). The approximate 10-fold increase in apical crypts with increasing Na + (Fig.9A) was also similar to that observed in F. heteroclitus when transferred from 1mmoll -1 Na + freshwater to 10PSU (~150mmoll -1 Na + ) brackish water (Scott et al, 2004).…”
Section: Transport In Cyprinodon Variegatussupporting
confidence: 79%
See 1 more Smart Citation
“…The extent of emergent MRC proliferation observed in C. v. variegatus and C. v. hubbsi is comparable to that observed in other euryhaline teleosts (Lee et al, 1996;Scott et al, 2004). The approximate 10-fold increase in apical crypts with increasing Na + (Fig.9A) was also similar to that observed in F. heteroclitus when transferred from 1mmoll -1 Na + freshwater to 10PSU (~150mmoll -1 Na + ) brackish water (Scott et al, 2004).…”
Section: Transport In Cyprinodon Variegatussupporting
confidence: 79%
“…However, C. v. variegatus have lower Na + uptake rates at a given MRC fractional area compared with C. v. hubbsi, indicating that the enhanced Na + uptake by C. v. hubbsi at low ambient Na thermodynamic questions regarding how such a system would function, but studies in goldfish (Preest et al, 2005) and tilapia (Hiroi et al, 2005) support the presence and function of NKCC whereas studies in zebrafish support the involvement of NCC (Esaki et al, 2007;Wang et al, 2009). In addition to variations in the proteins involved in Na + acquisition in freshwater fish gills, a number of studies have documented a variety of mitochondria-rich cell (MRC) types and dynamic responses of these cell types to changes in external ion concentrations (Chang et al, 2001;Fernandes et al, 1998;Greco et al, 1996;Hirai et al, 1999;Lee et al, 1996). Several studies, particularly in tilapia, have also co-localized specific apical proteins to specific MRC types (Hiroi et al, 2005;Inokuchi et al, 2009), and in general a strong relationship between the fractional area of MRC on the gill and Na + uptake capacity has been demonstrated for a number of fish species (Perry et al, 1992).…”
Section: ) Lakes In Central Florida Is Now Designated As a Subspeciesmentioning
confidence: 99%
“…Although in some FW-acclimated euryhaline fish NKIR cells are distributed in epithelia of both gill filaments and lamellae (Sakamoto et al, 2001;Lin et al, 2006), the pufferfish NKIR cells were normally observed in filament epithelia of both FW-or SW-acclimated individuals (Fig. 5B,E) (Lin et al, 2004b), similar to the situation in tilapia (Lee et al, 1996;Lee et al, 2003;Uchida et al, 2000). Hence, the colocalization of pFXYD and NKA suggests that pFXYD may interact with NKA at the basolateral membrane of MR cells in gill filaments of pufferfish.…”
Section: P-j Wang and Otherssupporting
confidence: 65%
“…By examining the effects of environmental salinity or ion levels and exogenous hormones on the density of α and β MR cells (Pisam et al, 1993), β MR cells were suggested to be associated with Ca 2+ uptake while α MR cells exerted dual functions: Cl -secretion in SW and Na + uptake in FW (Pisam et al, 1993;Pisam et al, 1995), but no ion-influx data are available to support their inference. Hwang's group classified three subtypes of MR cells, wavy-convex, shallow-basin and deep-hole types, in FW tilapia gills according to the morphologies of the apical openings (Lee et al, 1996), and subsequent physiological studies suggested roles for the three types of cells in Cl -uptake, Ca 2+ uptake and Cl -secretion, respectively, based on the correlations between the gill cell density of the three ionocyte types and ion (Na + , Cl -and Ca 2+ ) influxes (Tsai and Hwang, 1998;Chang et al, 2001;Chang et al, 2003). However, further functional analyses of those ionocytes are difficult due to limitations in the applicability of molecular physiological approaches to these anatomically or morphologically identified ionocytes.…”
Section: Comparison Of Ionocytes Between Speciesmentioning
confidence: 99%